The Intention to Use QRIS Among MSMEs in Rempoa Subdistrict, South Tangerang: The Influence of Perceived Ease of Use and Perceived Security with User Attitude as a Mediating Variable - Frimayasa, Agtovia; Suprayitno, Agung (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study investigates the influence of perceived ease of use and perceived security on the intention to use QRIS (Quick Response Code Indonesian Standard) among micro, small, and medium enterprises (MSMEs) in Rempoa Subdistrict, South Tangerang, with user attitude as a mediating variable. Using a quantitative approach and Partial Least Squares–Structural Equation Modeling (PLS-SEM) via SmartPLS, data were collected from 50 MSME respondents selected through purposive sampling. The research instrument was based on the Technology Acceptance Model (TAM) and tested for validity and reliability. The findings reveal that both perceived security and perceived ease of use positively and significantly influence user attitude and intention to use QRIS. User attitude significantly mediates these relationships, especially between perceived security and intention. The R² and Q² values indicate strong explanatory and predictive power of the model. These results suggest the need for strategies that enhance security perceptions and promote positive user attitudes to support wider QRIS adoption among MSMEs.